(3eNJUQ YLGFH GdOfjGs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
" (3GdMeO ddg HGQF GdeSehcGJ hQGRb GdeNdhbGJEdN (B" s
(3GdfSNI HgG MhGTs
(3PcQ ajg CSQGQ GdWHGFY hCUfGa GdNdb hZQGFH eG UfYhGCdNs
(3cJH Ydi GdfSNI Cf GSe GdcJGH (B" (3eNJUQ YLGFH GdOfjG ddeSYhOi (B" (3hGdJUhjH ef cTa GdXfhfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs